Experimental Validation of Feedback PI Controllers for Multi-Rotor Wind Energy Conversion Systems - Mourad Yessef; Habib Benbouhenni; Mohammed Taoussi; Ahmed Lagrioui; Ilhami Colak; Badre Bossoufi; Thamer A. H. Alghamdi (IEEE Access, 2024)
This new paper describes an experimental investigation of a proportional-integral (PI) controller that uses feedback control to regulate an energy system that uses multi-rotor wind energy systems. Pulse width modulation (PWM) is used by the proposed controller to control the power of the doubly-fed induction generator controlled by direct power control (DPC), which is intended to regulate and control the inverter. The proposed strategy differs from the traditional DPC strategy. The proposed control was studied in the case of variable wind speed, where the MATLAB and Dspace 1104 environment was used to implement this proposed feedback PI (FPI) controller, with a comparison with the proposed control technique and some existing works. The suggested FPI controller outperforms the traditional controller and certain other controllers in terms of lowering energy ripples, overshoot, steady-state error (SSE), response time, and the total harmonic distortion (THD) of supplied system currents, as demonstrated by experimental and simulation results. The THD value of current was reduced by 64.86% and 69.44% in the two proposed tests compared to the traditional DPC technique. Also, the value of ripples and overshoot of active power was reduced compared to the DPC method by 95.42% and 90.86%, respectively, in the case of step wind speeds. Moreover, ripples and SSE of reactive powers compared to the DPC technique were reduced by 37.51% and 84.13%, respectively. These high ratios indicate the high performance of the proposed DPC-FPI technique in enhancing the features of the system in contrast to the conventional DPC technique.